2002
DOI: 10.1097/00001813-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine and cisplatin in chemonaive patients with advanced epithelial ovarian cancer

Abstract: This phase II study evaluated the activity of gemcitabine (Gemzar) plus cisplatin (Platinol) as first-line treatment of advanced epithelial ovarian cancer. Forty-two chemonaive patients with advanced (stage III and IV) epithelial ovarian cancer received gemcitabine 1,250 mg/m(2) on days 1 and 8 and cisplatin 100 mg/m(2) on day 1, every 3 weeks, up to eight cycles. The median number of cycles completed was 5 (range 2-8). Of the 41 patients evaluable for tumor response, 20 had a partial response and nine had a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The synergy (10 -12) and clinical activity of systemic cisplatin and gemcitabine in patients with ovarian cancer are well described both in the chemotherapy-naive and relapse populations (13,14). Several characteristics of gemcitabine have suggested that it is a reasonable candidate for exploration in the i.p.…”
Section: Introductionmentioning
confidence: 99%
“…The synergy (10 -12) and clinical activity of systemic cisplatin and gemcitabine in patients with ovarian cancer are well described both in the chemotherapy-naive and relapse populations (13,14). Several characteristics of gemcitabine have suggested that it is a reasonable candidate for exploration in the i.p.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, our results are very similar to the experience of Bauknecht et al , who, in a phase II study with gemcitabine and cisplatin as first‐line treatment of people older than 60 years with FIGO stage IIIC or stage IV epithelial ovarian carcinoma, found an overall response rate of 62.2% (95% CI, 44.8–77.5%) and a median survival of 27.7 months (95% CI, 14.3–40.8 months) 18 . Also, Nogue et al reported a similar study with gemcitabine and cisplatin, with an overall clinical response rate of 70.7% (95% CI 56.8–84.6%), a median overall survival of 23.4 months (95% CI 15.9–29.9 months) and a median progression‐free survival time of 10.4 months (95% CI 9.4–13.5 months) 19 . In this respect, our study suggests that the combination of gemcitabine and carboplatin seems to be as efficacious as combined gemcitabine and cisplatin; in the same way, paclitaxel and carboplatin is equally efficacious as paclitaxel and cisplatin 20…”
Section: Discussionmentioning
confidence: 82%
“…In NSCLC, the use of a 3 weekly regimen results in significantly fewer dose delays and reductions (19 vs 51%), improved dose intensity, similar response rates and reduced grade 3/4 thrombocytopenia (6 vs 30%) than a 4 weekly one. This combination has also been tested in ovarian cancer (Nogue et al, 2002), transitional cell carcinoma (Lorusso et al, 2000) and pancreatic cancer. In the latter, a response rate of 11% was observed with stable disease in 57% (Heinemann et al, 2000).…”
Section: à2mentioning
confidence: 99%